Routine Chest Radiograph Interpretation Skills of Medical Officers at an Outpatient Setting - Norwati, Daud; Harmy, Mohamed Yusoff; Mohd Ezane, Aziz (2018)
In Malaysia, chest radiograph is a part of compulsory investigations during routine medical examination. Majority of these chest radiographs are interpreted by medical officers at the outpatient clinic. This study was to determine the concordance of chest radiograph interpretations between medical officers and radiologist. Medical officers‟ report of routine chest radiographs at the outpatient clinic Hospital Universiti Sains Malaysia over a 6-month period were compared to that of a radiologist. Of 408 chest radiographs reported, the concordance of interpretation between medical officers and radiologist was 93.6% (382 of 408). Medical officers correctly interpret 98.2% (378/385) of normal chest radiograph compared to 17.4% of abnormal chest radiographs (4/23). Therefore, routine chest radiograph interpretations of normal radiographs by medical officers were generally accurate. However, they were weak in interpreting abnormal chest radiographs. Medical officers need to be trained on detecting abnormalities on chest X-ray since most routine chest X-ray reporting is done based on their interpretation.